Interspecies Organogenesis for Human Transplantation. Issue 9 (September 2019) - Crane, Andrew T.; Aravalli, Rajagopal N.; Asakura, Atsushi; Grande, Andrew W.; Krishna, Venkatramana D.; Carlson, Daniel F.; Cheeran, Maxim C.-J.; Danczyk, Georgette; Dutton, James R.; Hackett, Perry B.; Hu, Wei-Shou; Li, Ling; et al.
Blastocyst complementation combined with gene editing is an emerging approach in the field of regenerative medicine that could potentially solve the worldwide problem of organ shortages for transplantation. In theory, blastocyst complementation can generate fully functional human organs or tissues, grown within genetically engineered livestock animals. Targeted deletion of a specific gene(s) using gene editing to cause deficiencies in organ development can open a niche for human stem cells to occupy, thus generating human tissues. Within this review, we will focus on the pancreas, liver, heart, kidney, lung, and skeletal muscle, as well as cells of the immune and nervous systems. Within each of these organ systems, we identify and discuss (i) the common causes of organ failure; (ii) the current state of regenerative therapies; and (iii) the candidate genes to knockout and enable specific exogenous organ development via the use of blastocyst complementation. We also highlight some of the current barriers limiting the success of blastocyst complementation.